The Influence Of K-Pop Idol On Student Lifestyle - Sembiring, Ziah Lestari; Daulay, Annisa Arrumaisyah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to determine the effect of K-POP Idol on student lifestyles. In this study, a qualitative approach was used with this type of descriptive research because the research is based on the philosophy of Postpositivism, used to examine natural object conditions, (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combination). , data analysis is inductive/qualitative in nature, and the results of qualitative research emphasize the meaning of generalizations. The subjects in this study were Islamic counseling guidance students from the Da'wah and Communication Faculty. This study uses purposive sampling as a procedure for selecting subjects or informants. The results of the research are regarding Hallyu and its phenomena in Indonesia, especially among students and the influence of Hallyu on student lifestyles which in this study describes data that shows their lifestyle tends to be consumptive, hedonic, and does not make good use of free time. 8 out of 10 interviewees answered that their behavior to buy merchandise was included in consumptive behavior, while 2 other interviewees answered that their behavior was not included in consumptive behavior. The interviewees who answered that their behavior was classified as consumptive thought that because when they bought merchandise they spent a lot of money, felt they had to buy every time their idol took out merchandise, bought something that was not a need but only a wish, making themselves more curious about things they had never seen before. owned and foster a sense of panic buying. Some of them are aware that buying a quota to stream the idol's content and buying merchandise is wasteful, but they argue that this is only for entertainment and to entertain them when they are tired of the existing routine.